2022
DOI: 10.1002/osp4.608
|View full text |Cite
|
Sign up to set email alerts
|

Association between fat‐infiltrated axillary lymph nodes on screening mammography and cardiometabolic disease

Abstract: Objective: Ectopic fat deposition within and around organs is a stronger predictor of cardiometabolic disease status than body mass index (BMI). Fat deposition within the lymphatic system is poorly understood. This study examined the association between the prevalence of cardiometabolic disease and ectopic fat deposition within axillary lymph nodes (LNs) visualized on screening mammograms. Methods:A cross-sectional study was conducted on 834 women presenting for fullfield digital screening mammography. The sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A recent case□control study of 431 obese breast cancer patients further showed that patients with enlarged fat-infiltrated contralateral axillary LNs on breast MRI and mammography had a higher risk of ipsilateral breast cancer nodal metastases, independent of patients’ age, BMI, and tumor characteristics 9 . Another recent study reported a positive association between fat-infiltrated axillary LNs and the prevalence of type 2 diabetes (T2DM) in women with obesity, independent of age and BMI, and confirmed that fat-infiltrated LNs are more commonly seen in women with obesity 10 . A smaller study recently reported a decrease in serum lipids in obese women who had a reduction in the size of fatty nodes after bariatric surgery, raising the possibility that fatty LNs are a modifiable risk factor for cardiometabolic disease among people with obesity 12 .…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…A recent case□control study of 431 obese breast cancer patients further showed that patients with enlarged fat-infiltrated contralateral axillary LNs on breast MRI and mammography had a higher risk of ipsilateral breast cancer nodal metastases, independent of patients’ age, BMI, and tumor characteristics 9 . Another recent study reported a positive association between fat-infiltrated axillary LNs and the prevalence of type 2 diabetes (T2DM) in women with obesity, independent of age and BMI, and confirmed that fat-infiltrated LNs are more commonly seen in women with obesity 10 . A smaller study recently reported a decrease in serum lipids in obese women who had a reduction in the size of fatty nodes after bariatric surgery, raising the possibility that fatty LNs are a modifiable risk factor for cardiometabolic disease among people with obesity 12 .…”
Section: Introductionmentioning
confidence: 76%
“…The internal dataset used for this study included 886 full-field digital screening mammogram (FFDM) mediolateral oblique (MLO) views with detectable axillary LNs collected through a retrospective review of screening mammograms over an 8-month period at a tertiary care academic medical facility. The detailed data collection process is described in a previous study 10 . In brief, the largest visible axillary LN on the left or right MLO view was measured and labeled, with a final assessment achieved via a consensus review between two radiology reviewers 9 .…”
Section: Data Source For Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation